Classical coins at the Cape: a history and catalogue of the Greek and Roman numismatic collections in Iziko Museums of South Africa - Nissen, Leigh (School of Languages and Literatures, 2025)
The collection of ancient Greek and Roman coins held by Iziko Museums of South Africa has been a part of the museum's primary collections since the South African Museum's inception in 1825. Over the years, this numismatic collection has developed via donations (for example those by Hajee Sullaiman Shah Mahomed); loans (such as the Mann Collection), and by various purchases made by the curators of the numismatic department itself. To date no complete catalogue or sylloge exists. Based upon the museum's own accession registers, archival research, and physical examination of the collection, this dissertation provides the first complete catalogue of the Greek and Roman coins in the museum's holdings. In doing so, a brief history of the establishment of the museum is given, along with its collecting practices of ancient coinage; a history of the numismatic department; and a history of numismatic display and curation in the museum, as far as this has been possible from the museum's own archival records, letters, and unpublished notes. In providing the first, accessible catalogue and history of the Greek and Roman coins in the museum, this dissertation also enters current conversations around curation, conservation, and display within museum spaces in South Africa and suggests future possibilities for antiquities collections of this nature within museum spaces in the country more generally.